Digital Advertising and the Challenge of Advertising Saturation for Entrepreneurs (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
It is already a reality that the internet has displaced traditional media. Its rapid evolution has modified the way humans communicate and interact with the world (Noguez, 2016). Likewise, it has affected fields as diverse as medicine, economics, politics, advertising, etc. Precisely, the combination of advertising and the digital world has resulted in more interactive, diverse, and specialized ads. Its effectiveness as a medium has led to exponential growth in digital advertising investments in recent years.However, there is a problem that already affected analog media and continues in the digital realm: advertising saturation. This can be defined as an excess of advertising messages in a given medium, which generates indifference in consumers and consequently reduces its effectiveness.This article aims to analyze, through a literature review, the impact of advertising saturation on the internet audience. The goal is to determine its effects on advertising effectiveness.